Create.ED : Strengthening Learning and Teaching in the Create Arts Disciplines : External Evaluation Report. - Goody, Allan (Office for Learning and Teaching, 2011)
This is an evaluation report of the CreateED project, which aimed to strengthen learning and teaching across Australian creative arts disciplines, including architecture, creative writing, design, performing arts (dance and music), and visual arts. The evaluation determined: the extent to which the project achieved its intended outcomes; strengths and challenges of the project management process; utility of the deliverables from the project for the relevant stakeholders; and success of the dissemination strategies.